MENGUKUR TINGKAT KEPUASAN WAJIB PAJAK TERHADAP LAYANAN PERPAJAKAN DI KANTOR PELAYANAN PAJAK MADYA DENPASAR - I Gede Suryantara; Setyawan, I Gusti Made (Polytechnic of State Finance STAN, 2023)
This research was conducted with the aim of measuring the quality of tax services at Kantor Pelayanan Pajak (KPP) Madya Denpasar with an emphasis on the level of satisfaction of taxpayers in obtaining tax services. The research method was carried out through a survey of 516 taxpayers who registered at the KPP Madya Denpasar and carried out in the first quarter, starting from January to March 2023. The research results were grouped into 5 (five) dimensions of service quality, tangibles (satisfaction with supporting facilities and infrastructure), reliability (employee reliability in providing services), responsiveness (speed of providing services), assurance (politeness and friendliness of employees), and empathy (handling service user complaints). This research is carried out periodically to maintain quality and improve tax services that are not yet optimal. This is in line with the commitment of KPP Madya Denpasar in maintaining the quality of tax services in a sustainable manner and it can give an impact on taxpayer compliance in fulfilling tax obligations.